The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/infdis/jiv306
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Inhibitory Receptors on T Cells DuringPlasmodium vivaxMalaria Impairs Cytokine Production

Abstract: The function and regulation of the immune response triggered during malaria is complex and poorly understood, and there is a particular paucity of studies conducted in humans infected with Plasmodium vivax. While it has been proposed that T-cell-effector responses are crucial for protection against blood-stage malaria in mice, the mechanisms behind this in humans remain poorly understood. Experimental models of malaria have shown that the regulatory molecules, cytotoxic T-lymphocyte attenuator-4 (CTLA-4), lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 51 publications
7
47
0
Order By: Relevance
“…Importantly, increased expression of both PD-1 and LAG-3 as a consequence of persistent Plasmodium falciparum infection has been confirmed in a cohort of Kenyan children [23]. Additionally, simultaneous blockade of CTLA-4, PD-1 and TIM-3 was shown to substantially improve the functionality of CD8 T cells, as measured by ex vivo cytokine production upon antigen stimulation [24]. Although it is possible that the lack of sterilizing protection upon natural exposure is due to functional exhaustion of CD8 T cells, further studies are required to clarify the biological mechanisms underlying these observations.…”
Section: Current Opinion In Immunologymentioning
confidence: 81%
“…Importantly, increased expression of both PD-1 and LAG-3 as a consequence of persistent Plasmodium falciparum infection has been confirmed in a cohort of Kenyan children [23]. Additionally, simultaneous blockade of CTLA-4, PD-1 and TIM-3 was shown to substantially improve the functionality of CD8 T cells, as measured by ex vivo cytokine production upon antigen stimulation [24]. Although it is possible that the lack of sterilizing protection upon natural exposure is due to functional exhaustion of CD8 T cells, further studies are required to clarify the biological mechanisms underlying these observations.…”
Section: Current Opinion In Immunologymentioning
confidence: 81%
“…falciparum , express higher levels of CTLA4 and PD1 on their T cells than uninfected or unexposed control subjects [24, 2628]. This increased expression has been proposed to be a sign of T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that CTLA4 and PD1 are also upregulated on the T cells of patients with acute malaria or children that are regularly exposed to P . falciparum in endemic areas [24, 2628]. However, it remains unclear how the expression of these coinhibitory receptors influences the immune response to acute P .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, improved T cell responses to malaria parasites both ex-vivo and in vivo can be induced by the simultaneous blockade of CTLA-4 and other inhibitory receptors, e.g . lymphocyte activation gene-3 (LAG-3), programmed death-1 (PD-1) and T cell immunoglobulin mucin-3 (TIM-3) [4850]. Moreover, enhancing OX40 signaling with agonist antibodies improved effector T cell responses, antibody production, and parasite clearance in experimental murine malaria [36].…”
Section: Discussionmentioning
confidence: 99%